Architectural fragments carved with human figures on Harsha Hill - Temples of India Project Team (Jio Institute, 2024)
It seems that the beam, richly carved with human figures, was probably placed on the varandika of the temple, the adjoining portions between the temple walls and the spire. The protruding offsets typically feature mithuna figures inside the niches, while the recess between the two offsets is beautifully carved with images of apsaras or women engaged in various activities. The male figures are often depicted with weapons and in the company of female companions. This fragment is one of the loose architectural fragments on Harsha Hill.